Technical progress, capital accumulation, and distribution - Naoki Yoshihara; Roberto Veneziani (University of Massachusetts, Department of Economics, 2019)
We study the effects of innovations on income distribution in capitalist economies characterised by a drive to accumulate. Consistent with the basic intuitions of Marx's theory of technical change, we show that there is no obvious relation between ex-ante profitable innovations and the income distribution that actually emerges in equilibrium, and individually rational choices of technique do not necessarily lead to optimal outcomes. Innovations may even cause the disappearance of all equilibria. Methodologically, it is not possible to fully understand the 'creative destruction' induced by innovations without capturing the dialectic between individual choices and aggregate outcomes, and the complex network of relations typical of capitalist economies.
Keywords: O33; D33; B51; 330; technical change; income distribution; profit rate